A Platelet Acquired Storage Pool Disorder Associated with Tamoxifen Therapy - Nayak, Lalitha; Schmaier, Alvin H. (Case Reports in Hematology, 2012)
The antiestrogenic drug tamoxifen, used in patients with breast cancer, is associated with an increase in arterial and venous thrombotic events, the mechanism of which is not clearly understood. We report a case of a lady who presented with new bruising and prolonged bleeding following a tooth extraction 4–6 weeks after starting tamoxifen. Investigations were consistent with an acquired platelet storage pool disorder. Repeat platelet function analysis was normal, performed 3 months after discontinuation of tamoxifen. We present a previously clinically unreported effect of tamoxifen on platelet function.